MENGENAL ṢIGAT-ṢIGAT DALAM MEREPRESENTASIKAN HADIS: - Mulizar (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2019)
In terms of sanad and matan, or based on the strengths and weaknesses, the Hadith is divided into two groups, namely: the hadith maqbūl and the hadith mardūd. One way to find out a hadith whether the hadith is accepted or mardūd can be seen from the Ṣīgāt. Ṣīgāt Hadith is divided into two groups, namely Ṣīgāt Jazm and Ṣīgāt Tamrῑḍ. An assessment of a Hadith is incomplete if we have not discussed ṣīgāt al-Jazm and ṣīgāt at-Tamrῑḍ. This needs to be done to understand how the Hadith is classified. In determining the laws of ṣīgāt al-Jazm and ṣīgāt at-Tamrῑḍ the Ulama of Hadith have explained that if the Hadith is a hadith ḍa’īf, then it is not allowed to exchange it with active sentences ( ṣīgāt al-jazm) such as: said the Messenger of Allah. mention the narration of the hadith ḍa’īf from the tabiin circles by using ṣīgāt al-jazm, but by using ṣīgāt at-tamrῑḍ as the words qῑla, ruwiya, ḥukiya and so forth. This article provides knowledge to the reader, namely how to recognize the traditions through the ṣīgāt expressed in a hadith and give insight to the traditions that are ambiguous and mardūd through ṣīgāt in a hadith, and express how the opinion of the hadith scholars about the ṣīgāt.